Nolo's guide to social security disability : getting & keeping your benefits - Morton, David A., 1945- (Berkeley, Calif. : Nolo, 2012)
"Explains what Social Security disability is and how to qualify, apply and retain benefits"--Provided by publisher.
What is social security disability? -- Applying for disability benefits -- Disability benefits for children -- Getting benefits during the application process (SSI) -- Proving you are disabled -- Who decides your claim? -- How claims are decided -- If you can do some work: your RFC -- How age, education, and work experience matter -- When benefits begin -- Reasons you may be denied benefits -- Appealing if your claim is denied -- Once you are approved -- Continuing disability review -- Your right to representation.
Includes bibliographical references and index.
Keywords: Disability insurance -- United States -- Handbooks, manuals, etc; Social security -- United States -- Handbooks, manuals, etc